Asymmetric Spillover Effect of The United States and China Islamic Index on ASEAN Islamic Index during The Covid-19 Pandemic - Achmad Jufri; Masriani Adhillah; Abdul Qoyum (Universitas Airlangga, 2022)
ABSTRAK Penelitian ini bertujuan untuk menguji spillover effect indeks saham syariah Amerika Serikat dan Cina terhadap indeks saham syariah ASEAN dengan menggunakan metode Nonlinier Autoregressive Distributed Lag (NARDL) untuk menemukan spillover effect yang bersifat asimetris selama pandemi Covid-19. Data yang diamati dimulai pada 1 Januari 2020 sampai dengan 30 September 2021 dengan total observasi sebanyak 336 data untuk masing-masing indeks saham. Penelitian ini mendapatkan beberapa temuan. Pertama, indeks saham syariah Amerika Serikat dan Cina memiliki pengaruh asimetris jangka pendek terhadap indeks saham syariah Indonesia, Malaysia dan Thailand selama pandemi Covid-19. Kedua, indeks saham syariah Amerika Serikat dan Cina hanya memiliki pengaruh asimetris jangka panjang terhadap indeks saham syariah Malaysia selama pandemi Covid-19. Ketiga, efek ketika terjadi penurunan indeks saham syariah Amerika Serikat dan Cina lebih besar dibandingkan pada saat terjadi kenaikan terhadap indeks saham syariah Malaysia selama pandemi Covid-19. Salah satu penyebab hubungan tersebut adalah karena adanya hubungan dagang yang sangat erat antara Amerika Serikat dan Cina terhadap Malaysia. Adapun implikasi dari penelitian ini adalah investor internasional dapat menjadikan hasil penelitian ini sebagai bahan pengambilan keputusan apabila terjadi kontraksi akibat krisis seperti pada saat pandemi Covid-19 terhadap indeks saham syariah Amerika Serikat dan Cina untuk mempertahankan maupun menjual portofolio investasi mereka. Kata Kunci: Spillover, Indeks Syariah, Asimetris, Covid-19. ABSTRACT This study aims to examine the spillover effect of Islamic stock indexes of the United States and China on the ASEAN Islamic stock index using the Nonlinear Autoregressive Distributed Lag (NARDL) method to find asymmetric spillover effects during the Covid-19 pandemic. The observed data starts on January 1, 2020, until September 30, 2021, with a total of 336 observations for each stock index. This study found some findings. First, the Islamic stock indexes of the United States and China have a short-term asymmetric influence on the Islamic stock indices of Indonesia, Malaysia, and Thailand during the Covid-19 pandemic. Second, the Islamic stock indexes of the United States and China have only a long-term asymmetric influence on Malaysia's sharia stock indexes during the Covid-19 pandemic. Third, the effect when there is a decline in Islamic stock indexes of the United States and China is greater than when there is an increase in the Malaysian sharia stock index during the Covid-19 pandemic. One of the reasons for this relationship is the very close trade relationship between the United States and China with Malaysia. The research implication of this study is that international investors can use the results of this research as a decision-making material in the event of a contraction due to the crisis (one of which is the Covid-19 pandemic) in the United States and China Islamic stock indexes to maintain or sell their investment portfolios. Keywords: Spillover, Islamic Index, Asymmetric, Covid-19. DAFTAR PUSTAKA Abdullahi, S. I. (2021). Islamic equities and covid-19 pandemic: Measuring Islamic stock indices correlation and volatility in period of crisis. Islamic Economic Studies, 29(1), 50-66. https://doi.org/10.1108/IES-09-2020-0037 Aslam, F., Mohmand, Y. T., Ferreira, P., Memon, B. A., Khan, M., & Khan, M. (2020). Network analysis of global stock markets at the beginning of the coronavirus disease (covid-19) outbreak. Borsa Istanbul Review, 20, 49–61. https://doi.org/10.1016/j.bir.2020.09.003 Azhar, J. A., Wulandari, R., & Kalijaga, U. I. N. S. (2021). Stock performance based on sharia stock screening: Comparasion between syariah stock indices of Indonesia and Malaysia. 1(1), 14–26. https://doi.org/10.20885/AMBR.vol1.iss1.art2 Baek, S., Mohanty, S. K., & Glambosky, M. (2020). Covid-19 and stock market volatility: An industry level analysis. Finance Research Letters, 37(January), 1-10. https://doi.org/https://doi.org/10.1016/j.frl.2020.101748 Dizioli, A., Guajardo, J., Klyuev, VladimirMano, R., & Raissi, M. (2016). Spillovers from China’s growth slowdown and rebalancing to the ASEAN-5 economies. IMF Working Papers, 16(170), 1. https://doi.org/10.5089/9781475524260.001 Forbes, K. J., & Rigobon, R. (2002). No contagion, only interdependence: Measuring stock market comovements. Journal of Finance, 57(5), 2223–2261. https://doi.org/10.1111/0022-1082.00494 Hasan, M. B., Mahi, M., Sarker, T., & Amin, M. R. (2021). Spillovers of the covid-19 pandemic: Impact on global economic activity, the stock market, and the energy sector. Journal of Risk and Financial Management, 14(5), 200. https://doi.org/10.3390/jrfm14050200 He, Q., Liu, J., Wang, S., & Yu, J. (2020). The impact of covid-19 on stock markets. Economic and Political Studies, 0(0), 275–288. https://doi.org/10.1080/20954816.2020.1757570 Hung, N. T. (2019). Return and volatility spillover across equity markets between China and Southeast Asian countries. Journal of Economics, Finance and Administrative Science, 24(47), 66–81. https://doi.org/10.1108/JEFAS-10-2018-0106 International Monetary Fund. (2021). Fault lines widen in the global recovery. World Economic Outlook Update, July 2021, 1–21. Retrieved from https://www.imf.org/en/Publications/WEO/Issues/2021/07/27/world-economic-outlook-update-july-2021 International Trade Administration. (2021). The investment climate statement chapter of the CCG is provided by the state department. Retrieved from https://www.trade.gov/country-commercial-guides/malaysia-market-overview Jebran, K., & Iqbal, A. (2016). Examining volatility spillover between Asian countries’ stock markets. China Finance and Economic Review, 4(1), 0–13. https://doi.org/10.1186/s40589-016-0031-1 Kayo, E. S. (2021). Bursa saham terbesar di dunia (20 besar). Retrieved from https://www.sahamu.com/bursa-saham-terbesar-di-dunia/ Kirkulak Uludag, B., & Khurshid, M. (2019). Volatility spillover from the Chinese stock market to E7 and G7 stock markets. Journal of Economic Studies, 46(1), 90–105. https://doi.org/10.1108/JES-01-2017-0014 Komorek, C. (2021). Record trade between Malaysia and China. Retrieved from http://www.fruitnet.com/asiafruit/article/184345/record-trade-between-malaysia-and-china Lee, H. Y. (2012). Contagion in international stock markets during the sub prime mortgage crisis. International Journal of Economics and Financial Issues, 2(1), 41–53. Lee, K.-J., Lu, S.-L., & Shih, Y. (2018). Contagion effect of natural disaster and financial crisis events on international stock markets. Journal of Risk and Financial Management, 11(2), 16. https://doi.org/10.3390/jrfm11020016 Lento, C., & Gradojevic, N. (2021). S&P 500 index price spillovers around the covid-19 market meltdown. Journal of Risk and Financial Management, 14(7), 330. https://doi.org/10.3390/jrfm14070330 Liu, H., Manzoor, A., Wang, C., Zhang, L., & Manzoor, Z. (2020). The covid-19 outbreak and affected countries stock markets response. International Journal of Environmental Research and Public Health, 17(8), 1–19. https://doi.org/10.3390/ijerph17082800 Marçal, E. F., Prince, D. de, Zimmermann, B., Merlin, G., & Simões, O. (2020). Assessing global economic activity linkages: The role played by United States, Germany and China. EconomiA, 21(1), 38–56. https://doi.org/10.1016/j.econ.2020.01.001 Mata, M. N., Razali, M. N., Bentes, S. R., & Vieira, I. (2021). Volatility spillover effect of Aan-Asia’s property portfolio markets. Mathematics, 9(12), 1–20. https://doi.org/10.3390/math9121418 McMillan, D. G. (2020). Interrelation and spillover effects between stocks and bonds: Cross-market and cross-asset evidence. Studies in Economics and Finance, 37(3), 561-582. https://doi.org/10.1108/SEF-08-2019-0330 Panjaitan, Y., & Novel, R. (2021). Volatility spillover among Asian developed stock markets to Indonesia stock market during pandemic covid-19. Jurnal Keuangan dan Perbankan, 25(2), 342–354. https://doi.org/10.26905/jkdp.v25i2.5532 Pesaran, M. H., Shin, Y., & Smith, R. J. (2001). Bounds testing approaches to the analysis of level relationships. Journal of Applied Econometrics, 16, 289–326. Purbasari, I. (2019). Volatility spillover effects from the US and Japan to the ASEAN-5 markets and among the ASEAN-5 markets. Sains: Jurnal Manajemen dan Bisnis, 11(2), 293-331. https://doi.org/10.35448/jmb.v11i2.6064 Rahmayani, D., & Oktavilia, S. (2021). Does the covid-19 pandemic affect the stock market in Indonesia? Jurnal Ilmu Sosial dan Ilmu Politik, 24(1), 33–47. https://doi.org/10.22146/JSP.56432 Ramdhan, N., Yousop, N. L. M., Ahmad, Z., Abdullah, N. M. H., & Zabizi, A. Z. (2016). Stock market integration: The effect of leader and emerging market. Journal of Advanced Research in Business and Management Studies, 2(1), 1–10. Saleem, A., Bárczi, J., & Sági, J. (2021). Covid-19 and Islamic stock index: Evidence of market behavior and volatility persistence. Journal of Risk and Financial Management, 14(8), 389. https://doi.org/10.3390/jrfm14080389 Sari, L. K., Achsani, N. A., & Sartono, B. (2017). Volatility transmission of the main global stock return towards Indonesia. Bulletin of Monetary Economics and Banking, 20(2), 229–254. https://doi.org/10.21098/bemp.v20i2.813 Sekaran, U., & Bougie, R. (2018). Metode penelitian untuk bisnis. Jakarta: Salemba Empat. Setiawan, A., & Kartiasih, F. (2021). Contagion effect of Argentina and Turkey crisis to Asian countries, is it really happening? Jurnal Ekonomi dan Pembangunan Indonesia, 21(1), 59–76. https://doi.org/10.21002/jepi.v21i1.1333 Shin, Y., Yu, B., & Greenwood-Nimmo, M. (2012). Modelling asymmetric cointegration and dynamic multipliers in a nonlinear ARDL framework. SSRN Electronic Journal, 1–61. https://doi.org/10.2139/ssrn.1807745 Suppakittiwong, T., & Aimprasittichai, S. (2015). A study of a relationship between the U.S. stock market and emerging stock markets in Southeast Asia. Unpublished undergraduate thesis. Sweden: Linnaeus University. Sznajderska, A., & Kapuściński, M. (2019). The spillover effects of chinese economy on Southeast Asia and Oceania. NBP Working Paper Issue 315. Retrieved from https://www.nbp.pl/publikacje/materialy_i_studia/315_en.pdf Thai Hung, N. (2019). Equity market integration of China and Southeast Asian Countries: Further Evidence from MGARCH-ADCC and wavelet coherence analysis. Quantitative Finance and Economics, 3(2), 201–220. https://doi.org/10.3934/qfe.2019.2.201 Thomson Reuters Practical Law. (2021). International trade in goods and services in Malaysia: Overview. Retrieved from https://uk.practicallaw.thomsonreuters.com/w-017-9602?transitionType=Default&contextData=(sc.Default)&firstPage=true Trade between Malaysia and China reached new high in 2020 despite Covid. (2021). Retrieved from https://www.freshplaza.com/article/9293748/trade-between-malaysia-and-china-reached-new-high-in-2020-despite-covid/ United States Census Bureau. (2021). Trade in goods with Malaysia. Retrieved from https://www.census.gov/foreign-trade/balance/c5570.html Vo, X. V., & Tran, T. T. A. (2019). Modelling volatility spillovers from the US equity market to ASEAN stock markets. Pacific Basin Finance Journal, 59(February 2020), https://doi.org/10.1016/j.pacfin.2019.101246 Wang, Q., & Han, X. (2021). Spillover effects of the United States economic slowdown induced by COVID-19 pandemic on energy, economy, and environment in other countries. Environmental Research, 196(February). https://doi.org/10.1016/j.envres.2021.110936 Wycislak, S. (2014). Contagion effect and organization. European Scientific Journal, 10(1), 17–26. https://doi.org/10.19044/esj.2014.v10n1p%25p Yan, B., Stuart, L., Tu, A., & Zhang, Q. (2020). Analysis of the effect of covid-19 on the stock market and investing strategies. SSRN Electronic Journal. https://doi.org/10.2139/SSRN.3563380 Yan, C. (2020). COVID-19 Outbreak and stock prices: Evidence from China. SSRN Electronic Journal. https://doi.org/10.2139/SSRN.3574374 Yujing, O. (2021). China-Malaysia diplomatic relations – sailing towards a brighter future. Retrieved from https://www.thestar.com.my/opinion/letters/2021/05/31/china-malaysia-diplomatic-relations—sailing-towards-a-brighter-future